Hydroxychloroquine as Pre-exposure Prophylaxis for Coronavirus Disease 2019 (COVID-19) in Healthcare Workers: A Randomized Trial. (17th October 2020) - Rajasingham, Radha; Bangdiwala, Ananta S; Nicol, Melanie R; Skipper, Caleb P; Pastick, Katelyn A; Axelrod, Margaret L; Pullen, Matthew F; Nascene, Alanna A; Williams, Darlisha A; Engen, Nicole W; Okafor, Elizabeth C; Rini, Brian I; et al.
Abstract: Background: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a rapidly emerging virus causing the ongoing coronavirus disease 2019 (COVID-19) pandemic with no known effective prophylaxis. We investigated whether hydroxychloroquine could prevent SARS-CoV-2 in healthcare workers at high risk of exposure. Methods: We conducted a randomized, double-blind, placebo-controlled clinical trial of healthcare workers with ongoing exposure to persons with SARS-CoV-2, including those working in emergency departments, intensive care units, COVID-19 hospital wards, and first responders. Participants across the United States and in the Canadian province of Manitoba were randomized to hydroxychloroquine loading dose then 400 mg once or twice weekly for 12 weeks. The primary endpoint was confirmed or probable COVID-19–compatible illness. We measured hydroxychloroquine whole-blood concentrations. Results: We enrolled 1483 healthcare workers, of whom 79% reported performing aerosol-generating procedures. The incidence of COVID-19 (laboratory-confirmed or symptomatic compatible illness) was 0.27 events/person-year with once-weekly and 0.28 events/person-year with twice-weekly hydroxychloroquine compared with 0.38 events/person-year with placebo. For once-weekly hydroxychloroquine prophylaxis, the hazard ratio was .72 (95% CI, .44–1.16; P = .18) and for twice-weekly was .74 (95% CI, .46–1.19; P = .22) compared with placebo. Median hydroxychloroquine concentrations in whole blood were 98 ng/mL (IQR, 82–120) with once-weekly and 200 ng/mL (IQR, 159–258) with twice-weekly dosing. Hydroxychloroquine concentrations did not differ between participants who developed COVID-19–compatible illness (154 ng/mL) versus participants without COVID-19 (133 ng/mL; P = .08). Conclusions: Pre-exposure prophylaxis with hydroxychloroquine once or twice weekly did not significantly reduce laboratory-confirmed COVID-19 or COVID-19–compatible illness among healthcare workers. Clinical Trials Registration: Clinicaltrials.gov NCT04328467. Abstract : In this randomized clinical trial of 1483 high-risk healthcare workers, there was no significant reduction in incidence of COVID-19 with once-weekly or twice-weekly hydroxychloroquine compared with placebo.